PREBIOTICS IN INFANT FORMULAS - Yvan Vandenplas; I. N. Zakharova; Yu. A. Dmitrieva ("Paediatrician" Publishers LLC, 2015)
Microbiota of the gastrointestinal tract is different in breastfed infants and in children receiving standard infant formulas. While breast milk is rich in prebiotic oligosaccharides and can also contain some probiotics, standard infant formulas contain neither one thing nor the other. The formulation of an infant formula includes various prebiotic ingredients: galacto- and fructooligosaccharides, polydextrose and their combinations. There is evidence that the addition of prebiotics to baby food makes the microbiota of the gastrointestinal tract of infants receiving infant formulas more similar to the microbiota of breastfed children. Prebiotics alter the metabolic activity of the intestinal microflora (lower stool pH and increase the amount of short-chain fatty acids), have a bifidogenic effect and provide a stool consistency and bowel movement frequency that are similar to these parameters in breastfed infants. There is limited evidence that such changes in microbiota of the gastrointestinal tract may have some influence on the development of an infant's immune system. Adverse events are extremely rare in the application of prebiotics.